Repositioning Correctional Institutions as Strategic Pillars of the Integrated Criminal Justice System in Countering Narcotics Recidivism - Tajuddin, Mulyadi Alrianto (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2026)
The high number of narcotics-related recidivists in Indonesia reflects systemic failures in the rehabilitation of prisoners in prisons. Most cases of narcotics crimes involve repeat offenders, demonstrating a mismatch between the normative role of correctional institutions as an important part of the Integrated Criminal Justice System. The objectives of this study are to analyze the strategic position and role of correctional institutions in the Integrated Criminal Justice System in accordance with Law Number 22 of 2022, assess the challenges in implementing rehabilitation programs for inmates who have reoffended with narcotics, and formulate a model for repositioning correctional institutions to improve the prevention of narcotics law violations. The research method used is a juridical-normative approach by analyzing regulations, academic literature, and real data on recidivism that are analyzed in a descriptive-qualitative manner. The findings of the study show that the strategic position of correctional institutions is hampered by inconsistencies in implementation, which include prison overcapacity, limitations in human resources, absence of operational standards specific to procedures for recidivists, and inconsistent rehabilitation programs. These obstacles are multidimensional, including structural, normative, operational, and social and cultural aspects that together interfere with the effectiveness of rehabilitation. The novelty in this study is the development of a Risk-Need-Responsiveness model that is adjusted to the values of Pancasila and the Integrated Criminal Justice System, creating a repositioning model based on three stages of intervention: pre-coaching through the Integrated Assessment Team from the beginning of the investigation, coaching that is differentiated based on risk level, and post-coaching with a structured aftercare program. The research recommends phased implementation through pilot projects in selected narcotics prisons, as well as regulatory revisions to strengthen formal coordination mechanisms between subsystems.